Implikasi Perubahan Delik Formilke Materiil Dikaitkan Dengan Putusan Mk Nomor 25/Puu-Xiv/2016 Dalam Tindak Pidana Korupsi - Pane, Paisal Arifsa; Effendi, Erdianto; Rahmadan, Davit (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Based on the ruling of the Constitutional Court the number 25/PUU-XIV/2016 that States that theword "may" in article 2 paragraph (1) and article 3 of Act No. 20 Year 2001 is contrary to the basic law sothat the word "may" was abolished. This can have an impact to the process of law enforcement which wordscan be wiped out before, only a indication of the State financial losses can already be declared as a suspectafter the abolition of the Word can then State financial losses should be counted for sure. Law enforcementtends to wait for the calculation of the authorized agency according to the 1945 Constitution Article 23E toexamine management and responsible about the finances of the State held one of the Agency's financialInspectors free and independent, pertegas in the back with the law number 15 Year 2006 About AgencyFinancial Examiners.This type of research can be classified in types of normative research karna in the study related tothe law review principles of norms of the law, aiming to find out the impact of the mutusan MK number25/PUU-XIV/2016 and legal certainty State financial losses of post that verdict.Calculation of the financial losses of the country itself is often all be permaslaahan in the courtswhich related institutions which calculate the financial loss to the country. The fact that happens the Courtoften use the institutions other than the CPC, this will give rise to a debate that would be barriers againstlaw enforcement and the legal certainty of the financial state of the matter has not yet been fulfilled so thatthe law enforcement had been waiting for the results of the audit institution that authorities will havebarriers.With regard to the cases of post the verdict of law enforcement should be more meticulous inspecifying a person as a suspect because whenever the case is running before the ruling of theConstitutional Court were valid then after court ruling The Constitution that law enforcement mustcalculate the return loss of the State because it applies the principle of oportunitas which in article 1paragraph 2 of the CRIMINAL CODE States that when there is a change in the legislation after the deed isdone, then against the defendant the most advantageous conditions applied and calculating losses of Stateinstitutions must be designated precisely so that it will be able to harm the country.Keywords: Crime-Corruption